Analysis of The Influence of Information Technology on Construction Project Performance - Priambudi, Gayuh Wakhyu; Erick Dazki (INOVTEK Polbeng - Seri Informatika, 2024)
This research aims to examine the impact of information technology on the performance of construction projects, especially those focused on high-rise buildings carried out by PT QRS Development. The background of this research is based on the importance of information technology in increasing the efficiency and effectiveness of construction project management, considering the complexity and high risks involved in multi-storey building projects. This research uses a quantitative methodology with data collection carried out using regression analysis techniques. Research findings show that information technology has a positive influence, both individually and collectively, on the performance of multi-storey building construction projects at PT QRS Development. The conclusions of this research indicate that the application of information technology can increase efficiency and effectiveness in construction project management. The implication is that construction companies are advised to continue adopting and updating information technology to optimize their project performance.